Bovine SLC11A1 3´ UTR SSCP genotype evaluated by a macrophage in vitro killing assay employing a Brucella abortus strain - Martínez, R.; Toro R., R.; Montoya, F.; Burbano, M.; Tobón, J.; Gallego, J.; Dunner, J.; Cañón, J. (Blackwell Verlag, 2018)
The 3¢ untranslated region (3¢ UTR) of the bovine natural resistanceassociated macrophage gene (NRAMP1 or SLC11A1) was genotyped in Colombian Creole Blanco Orejinegro (BON) (Bos taurus) (n = 140) and Zebu Brahman (Bos indicus) (Z) (n = 20) cattle and their crosses (BON · Zebu Brahman [B · Z] [n = 10]; Zebu Brahman · BON [Z · B] [n = 10]), and in animals from a Holstein · BON (H · B) (n = 10) cross. Direct sequencing and single-strand conformation polymorphism analysis (SSCP) helped in detecting the polymorphic behaviour. The association between resistance to brucellosis infection and SSCP genotype was evaluated using a macrophage in vitro killing assay employing a virulent Brucella abortus strain. The 3¢ UTR (GT) repeated polymorphism was gentoyped and its association with resistance to brucellosis was evaluated. When all breeds were grouped, a high frequency in the homozygote GT12 (AA genotype) (0.823) and a very low frequency in the homozygote GT10 (BB genotype) (0.047) were detected. The BON (0.963), Z · B (0.60) and H · B (1.00) cattle showed high GT12 allele frequencies, unlike that seen for the B · Z and Zebu cattle (0.3002 and 0.218, respectively). The GT10 allele was only found in the Zebu cattle (0.391). A significant association (p < 0.001) was found between the B. abortus macrophage in vitro killing assay phenotypes and the bovine SLC11A1 3¢ UTR genotypes, which suggests that the A allele may be associated with resistance. Because only nine animals had the BB genotype, the results require some confirmation in more extensive populations.